Characterization of Sarir Sahara Soils in the Libyan Jamahiriya* - ABDELGAWAD, GILANI; RAHOMA, EZZEDEIN; BUSCH, W. (The Libyan Journal of Agriculture, 2023)
A study of the major soil series in the Sarir area, southeast of the Libyan Jamahiriya, disclosed a number of: (a) morphological features reflecting a minimum of pedogenic processes (aeolian as well as alluviation activities), (b) chemical data characterizing nonsaline, alkali soil conditions (with possible lithological discontinuities), and (c) mineralogical structures exhibiting domination of the clay fraction by expansible 2:1-layer silicates. Fibrous clays of the attapulgite (palygorskite) form appear to be present in these soils, but the evidence obtained is yet to be confirmed.